2018
DOI: 10.1016/j.cct.2017.12.014
|View full text |Cite
|
Sign up to set email alerts
|

Rationale, design and pilot feasibility results of a smartphone-assisted, mindfulness-based intervention for smokers with mood disorders: Project mSMART MIND

Abstract: The results from the feasibility study indicated high levels of acceptability and satisfaction with SMI-CM. The ongoing RCT will allow evaluation of the efficacy and mechanisms of action underlying SMI-CM for improving cessation rates among smokers with mood disorders.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
19
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 25 publications
(27 citation statements)
references
References 50 publications
0
19
0
Order By: Relevance
“…In addition, this study is consistent with previous smoking cessation app research in different types of SMI populations. For example, Minami et al 49 developed SMI-CM, a smoking cessation app for patients with mood disorders and tested its feasibility in a small sample. SMI-CM used a mindfulness and acceptance approach combined with contingency management to reinforce CO verified abstinence twice a day.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, this study is consistent with previous smoking cessation app research in different types of SMI populations. For example, Minami et al 49 developed SMI-CM, a smoking cessation app for patients with mood disorders and tested its feasibility in a small sample. SMI-CM used a mindfulness and acceptance approach combined with contingency management to reinforce CO verified abstinence twice a day.…”
Section: Discussionmentioning
confidence: 99%
“…These dimensions are also included in this review. Regarding the intervention integrity, thirteen studies scored in the 80–100% category [ 34 , 35 , 36 , 39 , 41 , 43 , 45 , 46 , 49 , 50 , 51 , 52 , 53 ], four in the 60–79% [ 40 , 44 , 48 , 54 ], two in the less than 60% [ 42 , 47 ], and five did not provide this information [ 32 , 33 , 37 , 38 , 55 ]. Concerning the analysis component, the unit of analysis and allocation were individuals except for Raiff et al [ 48 ], where it was pairs of smokers.…”
Section: Resultsmentioning
confidence: 99%
“…The remaining studies did not analyze point-assessment differences. Finally, two studies reported reductions in CPD [ 52 , 53 ].…”
Section: Resultsmentioning
confidence: 99%
“…Mobile phone-based smoking cessation interventions have proven to be a cost-effective tool for supporting smokers to quit smoking. Some studies also showed that mobile smoking cessation apps can create short-term impacts on helping smokers to quit smoking [8][9][10][11][12][13]. A recent study has shown that daily smokers using a behavioral, decision-aid smartphone app achieved 23.8% self-reported 3-month continuous abstinence [14].…”
Section: Mobile Smoking Cessationmentioning
confidence: 99%